2012
DOI: 10.1007/s10014-012-0088-y
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic onset of rhabdoid meningioma after initiating treatment for infertility

Abstract: Rhabdoid meningioma (RM) is a rare aggressive phenotype and is classified as a grade III neoplasm by the World Health Organization. A 29-year-old woman initiated treatment with clomiphene citrate for infertility. Two weeks later, she presented with acute headache and nausea. Brain computed tomography and magnetic resonance imaging demonstrated a tumor with hematoma in the left frontoparietal region. Surgical resection was performed, and the tumor was subtotally removed. The tumor was diagnosed as a rhabdoid me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Regarding histological classification, Grade II meningiomas included two clear cell meningiomas and one chordoid meningioma, and Grade III meningiomas included one papillary meningioma and one rhabdoid meningioma on which we have reported previously [7]. In this study, we included patients with HGMs that were transformed from benign (Grade I) meningiomas at first presentation.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding histological classification, Grade II meningiomas included two clear cell meningiomas and one chordoid meningioma, and Grade III meningiomas included one papillary meningioma and one rhabdoid meningioma on which we have reported previously [7]. In this study, we included patients with HGMs that were transformed from benign (Grade I) meningiomas at first presentation.…”
Section: Methodsmentioning
confidence: 99%
“…While studies investigating meningioma and fertility treatment are limited to retrospective case reports and one case-control study [10][11][12][13], the association of progesterone receptor expression and meningioma has been studied more extensively [30]. There are various situations in addition to fertility treatment where patients might be exposed to high dose estrogen or progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…One large case control study found no association between fertility treatment and meningioma [10]. There have been three cases of meningioma diagnosed in women with a history of fertility treatment described in the literature [11][12][13]. Recently, Wengel et al identified eight transgender patients who developed meningioma during hormone therapy.…”
Section: Introductionmentioning
confidence: 99%
“…One case, for instance, reported on a 37-year-old right-handed female, with a prior history of three cycles of fertility treatment, who presented with a massive parasagittal meningioma [5]. A 29-year-old female presented with acute hemorrhage of a rhabdoid meningioma two weeks after initiating treatments of clomiphene citrate [6]. Furthermore, there have been multiple cases of meningiomas with accelerated growth during pregnancy [7, 8].…”
Section: Discussionmentioning
confidence: 99%